Identifying Factors And Criminal Law Enforcement on Online Gambling: An Empirical Study - Alif Rifqi Subhan; Sukardi (Contemporary Issues in Criminal Law, 2024)
This study investigates the factors that lead to online gambling and the measures taken by police investigators to respond to the crime. This study employed empirical legal research focusing on the actual data and facts obtained from interviews with perpetrators and players of online gambling alongside the police investigators. This study revealed that various reasons exist in the commission of online gambling by the perpetrators, such as possessing desires for instant wealth, being burdened by debt, obtaining funds for a wedding, seeking enjoyment, curiosity, killing time, having no other better activities, and wanting to spend money. Based on the differential association theory, these reasons are linked to the lack of capability to serve as better human resources and bad habit as the internal factors; as well as economic motive and lack of the legal awareness of the perpetrators as the external factors. The measures taken by the police in response to the crime involves both preventive and repressive ones. The former is taken by conducting numerous campaigns in neighborhoods, schools, and other social gatherings to raise awareness, educate, and guide the community to prevent and eradicate gambling as a social disease. The latter is implemented when it has been proven that the accused perpetrator is involved in a crime, whereby they will be legally processed accordingly. In the enforcement of online gambling cases, Police has not yet applied the ITE Law but uses KUHP instead to charge the defendants. Hence, the specific regulations for handling online gambling cases have not been implemented. Keywords: Criminal law enforcement, Differential association theory, Online gambling, Police investigator. Abstrak Penelitian ini menyelidiki faktor-faktor penyebab perjudian online dan langkah-langkah yang diambil oleh penyelidik polisi untuk mengatasi kejahatan ini. Penelitian ini menggunakan penelitian hukum empiris yang berfokus pada data dan fakta aktual yang diperoleh dari wawancara dengan pelaku dan pemain judi online serta penyelidik polisi. Penelitian ini mengungkapkan bahwa berbagai alasan dipenuhi dalam melakukan judi online oleh para pelakunya seperti ingin cepat kaya, terbebani hutang, mencari dana untuk menikah, mencari kesenangan, rasa ingin tahu, menghabiskan waktu, tidak memiliki kegiatan lain, dan menghabiskan uang. Dari teori asosiasi diferensial, alasan-alasan ini terkait dengan kurangnya kemampuan sumber daya manusia dan kebiasaan sebagai faktor internal, serta motif ekonomi dan kurangnya kesadaran hukum pelaku sebagai faktor eksternal. Tindakan polisi melibatkan tindakan preventif dan represif untuk menangani kejahatan ini. Yang pertama diambil dengan melakukan berbagai kampanye di lingkungan, sekolah, dan pertemuan sosial lainnya untuk meningkatkan kesadaran, mendidik, dan membimbing masyarakat untuk mencegah dan memberantas penyakit sosial seperti perjudian. Yang terakhir ini dilaksanakan ketika telah terbukti bahwa pelaku yang dituduh terlibat dalam kejahatan, dan mereka akan diproses secara hukum sesuai dengan itu. Dalam penegakan kasus perjudian online, Polisi belum menerapkan UU ITE melainkan menggunakan KUHP untuk menuntut para terdakwa. Oleh karena itu, peraturan khusus untuk menangani kasus perjudian online belum diterapkan. Kata kunci: Penegakan hukum pidana, Teori asosiasi diferensial, Perjudian online, Penyidik polisi.